2005
DOI: 10.1175/jtech1765.1
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Wind Profiler Data in the Canadian Meteorological Centre’s Analysis Systems

Abstract: Real-time horizontal wind observations from the National Oceanic and Atmospheric Administration's (NOAA's) Profiler Network (NPN) are assessed in preparation for their assimilation in the Canadian Meteorological Centre (CMC) analysis systems. As a first step, radiosonde winds from 20 stations were compared to the central U.S. profiler stations over the 2001/02 winter season. It was found that profilers are at least as good as conventional radiosonde data. The 2001/02 winter season data were also used to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For weather balloons (referred to as ADPUPA in NCEP system), the data at 1000, 925, 850, 700, 500, 400, 300, 250, 200, 150, 100, 70, 50, and 10 hPa are used. Reports from aircraft and satellite retrievals are reduced to every fourth value and wind profilers to every third level [ St‐James and Laroch , ]. National Oceanic and Atmospheric Administration (NOAA) daily 1/4° Optimum Interpolation Sea Surface Temperature (OISST) version 2 [ Reynolds et al ., is used to provide the ocean and ice boundary conditions.…”
Section: Description Of Datamentioning
confidence: 99%
“…For weather balloons (referred to as ADPUPA in NCEP system), the data at 1000, 925, 850, 700, 500, 400, 300, 250, 200, 150, 100, 70, 50, and 10 hPa are used. Reports from aircraft and satellite retrievals are reduced to every fourth value and wind profilers to every third level [ St‐James and Laroch , ]. National Oceanic and Atmospheric Administration (NOAA) daily 1/4° Optimum Interpolation Sea Surface Temperature (OISST) version 2 [ Reynolds et al ., is used to provide the ocean and ice boundary conditions.…”
Section: Description Of Datamentioning
confidence: 99%
“…In the first experiment, denoted NO_RaOb, radiosonde (tEmP, PILOt and dropsondes reports) and wind profiler data are denied over North america. although the radiosonde stations and the NOaa wind profilers are distinct networks, we grouped them because the value of the wind profiler network in the mSC forecast systems has recently been evaluated (St-James and Laroche, 2005). It was shown that wind profilers, mainly located in the central united States and alaska, provide only a slight improvement, especially at short forecast ranges.…”
Section: Methodology a Experimental Designmentioning
confidence: 99%
“…The core of this system is the fully compressible non-hydrostatic model developed by COSMO (the Consortium for Small-Scale Modelling, currently composed of the national weather services of Germany, Switzerland, Italy, Greece, Poland, Romania and Russia -see http:// www.cosmo-model.org/. The COSMO model includes a full set of physical parameterizations suited for weather prediction applications (Steppeler et al, 2003). The Newtonian relaxation technique known as nudging (Schraff, 1997) is used to produce the initial conditions for each forecast; although simple, this method is an efficient way to nudge the state of the model towards the real state of the atmosphere.…”
Section: Model Developmentmentioning
confidence: 99%